Modeling and Simulation of Feedback based Linear Electromechanical actuator - et. al., Dr.B.Suresh Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An actuator is a device that which provides control over certain automation systems and also provides tuning in movement or positioning in various applications like manufacture of valves, motor, wastewater treatment plants, onboard electronics based on the type of configuration of type of actuators. Out of the available types of actuators, linear Electro Mechanical Actuators (EMA) is a powerful and advanced tool which provides optimal solution for the field of automation, various applications where high speed, high precision with control are required. This paper proposes to have velocity feedback system to entire function of EMA’s in order to improve its functionality, and thus enhances the efficiency. This paper also proposes modeling and simulation of normal conventional linear Electro Mechanical Actuator and velocity feedback controlled EMA and compares the results in MATLAB/SIMULINK.